2013
DOI: 10.1007/s00348-012-1441-y
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent friction drag reduction using electroactive polymer and electromagnetically driven surfaces

Abstract: This work reports aerodynamic testing of two spanwise-oscillating surfaces fabricated out of electroactive polymers (EAPs) in the dielectric form of actuation (DEA), and of an electromagnetic-driven linear motor. Hot-wire and PIV measurements of velocity and direct measurement of friction drag using a drag balance are presented. A maximum of 16% surface friction reduction, as calculated by the diminution of the wall-normal streamwise velocity gradient was obtained. Among other quantities, the spatial dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…Hot-wire measurements were then made in the turbulent boundary layer and the oscillations were found to produce a reduction in turbulent fluctuations. Similar experiments were carried out by Choi [13] and Gouder et al [14], who developed electromagnetic and electro-active polymer surfaces: both measured similar reductions in turbulent fluctuations as well as skin-friction drag reductions of 45 % and 17 % respectively. Gatti et al also conducted experiments using electro-active polymer surfaces and measured a drag reduction, integrated over the whole surface, of 2.4 % .…”
Section: Introductionsupporting
confidence: 70%
“…Hot-wire measurements were then made in the turbulent boundary layer and the oscillations were found to produce a reduction in turbulent fluctuations. Similar experiments were carried out by Choi [13] and Gouder et al [14], who developed electromagnetic and electro-active polymer surfaces: both measured similar reductions in turbulent fluctuations as well as skin-friction drag reductions of 45 % and 17 % respectively. Gatti et al also conducted experiments using electro-active polymer surfaces and measured a drag reduction, integrated over the whole surface, of 2.4 % .…”
Section: Introductionsupporting
confidence: 70%
“…Fukagata and Kasagi [54] showed that the drag reduction effect was lowered by approximately 10% at 75 wall units and 35% at 150 wall units downstream of the control region. A similar effect was shown by Gouder et al [31] over an electromagnetically driven surface, the drag reduction effect was reduced by 25% at 240 wall units downstream of the oscillating surface.…”
Section: Resultssupporting
confidence: 72%
“…Conducting hot-wire anemometry and particle-image velocimetry (PIV) as well as direct friction drag measurements via a force balance, Gouder et al [31] achieved a maximum drag reduction of 16% using electroactive polymers and electromagnetic linear motors to create a spanwise oscillating motion of the wall. Laadhari et al [32] excited the wall in the spanwise direction by a crankshaft system and detected that spanwise wall oscillations cause a sustained decrease of both turbulence intensities and Reynolds shear stress.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known, thanks for example to the FIK identity (Fukagata et al 2002), that the portion of Reynolds shear stresses located in the outer layer carries an increasing contribution to the skin-friction coefficient as Re increases. These Reynolds stresses are due to the very large turbulent structures (Ganapathisubramani et al 2003;Guala et al 2006) that populate the outer layer and modulate the smaller structures residing near the wall (Brown & Thomas 1977;Ganapathisubramani et al 2012;Lozano-Durán & Jiménez 2014b). This modulation has been confirmed also in the case of drag-reducing flows (see for example Touber & Leschziner 2012).…”
Section: Concluding Discussionmentioning
confidence: 58%
“…The streamwise-travelling waves, in particular, yield larger maximum drag reduction and, more importantly, improved energetic efficiency, which is essential if drag reduction is motivated by the need to save energy. Laboratory implementations of such techniques range from proof-of-principle experiments (Auteri et al 2010) to experiments with novel actuation technologies, such as electroactive polymers (Gouder et al 2013) or plasma actuators, specifically addressing the problem of actuation efficiency (Gatti et al 2015). Thanks to the wealth of data available for this class of forcing, it is known that the impressive low-Re performance, i.e.…”
Section: Introductionmentioning
confidence: 99%